The Role of Internal Audit in Assessing the Risks of Management Decisions regarding Strategic Operations )Acquisition) - Yousif, Najat Saleem; Mohamed, Safaa Ahmad (Journal of Economics and Administrative Sciences, 2022)
The research aims to verify the Role of Internal Auditing in Assessing the Risks of Strategic Operations (Acquisition) and then reflect on management decisions. Since all corporations wish to expand, growth and domination of the market may expose them to multiple risks that lead to failure. The research assumes two main hypotheses. First, there is no role for internal audit in evaluating the strategic operations (acquisition). Second, there is no relationship between internal auditing in assessing the risks of strategic operations (Acquisition) and management decisions. The data was collected by using a questionnaire distributed to a group of private bank employees. The statistical analysis regarding research rejected the two hypotheses and accepted the two alternative hypotheses, which stated that there is a role for internal audit in assessing the strategic operation’s risks (Acquisition) and that there is a significant relationship between internal auditing in assessing the risks of strategic operations (Acquisition) and management decisions. Among the most important conclusions reached is that an internal audit is so important in determining the risks regarding decision making for acquisition. The important recommendation is to activate the role of internal auditing regarding acquisition. The value of the research clarifies the role of internal auditing in assessing the risks of acquisition processes and encourages the adoption of the idea in the Iraqi environment. It’s considered as one of the recent research as it keeps pace with developments in the world